The Eu:CROPIS Mass Property Campaign: Trimming a Spin-Stabilized Compact Satellite for a Long-Term Artificial Gravity Experiment - Fabian Orlowski-Feldhusen; Sebastian Kottmeier; Ansgar Heidecker; Olaf Mierheim; Oliver Kolakowski; Robert Klöpper (International Journal of Aerospace Engineering)
Eu:CROPIS (Euglena Combined Regenerative Organic Food Production in Space) is the first mission of DLR’s compact satellite program. The launch of Eu:CROPIS took place on December 3rd in 2018 on-board the Falcon 9 SSO-A mission. The satellite’s primary payload Eu:CROPIS features a biological experiment in the context of closed loop coupled life support systems. The Eu:CROPIS satellite mission uses spin stabilization along its Z-axis to provide defined acceleration levels for the primary and secondary payloads to simulate either a Moon or Mars gravity environment. For the payload performance, it is vital to achieve a minimum deviation between spacecraft Z-axis and the major moment of inertia (MoI) axis to minimize the offset of the envisaged acceleration levels. Specific moment of inertia ratios between the spin- and minor axes had to be maintained to allow the attitude control system to keep the satellite at a stable rotation despite environmental disturbances. This paper presents the adaptive and flexible trimming strategy applied during the flight model production, as well as the mass property measurement acceptance campaign and the respective results.